Socio-Emotional Skills for Labor Market Outcomes in the Turkish Cypriot Community - World Bank (World Bank, Washington, DC, 2020)
The labor market of the Turkish Cypriot community (TCc) is characterized by low participation and low employment rates, especially among youth. A series of World Bank reports on the Turkish Cypriot (TC) labor market and higher education sector between 2016 and 2019 found a mismatch between the skills generated by the higher education system in the TCc and those in demand in the labor market. Socio-emotional skills are critical determinants of whether youth can work towards achieving their aspirations in the course of their education, and whether they are likely to find and sustain employment over the longer term. When questioned about the labor supply, employers in the TCc pointed to a lack of technical, interpersonal and socio-emotional skills among TC youth and students; this, in turn, reduces their employability due to their low productivity and effectiveness in the workplace. This remainder of this report contains sections on experimental design, data and empirical strategy, implementation, results, discussion and conclusion.